2017
DOI: 10.3389/fvets.2017.00205
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy Increases Growth Factor Release from Equine Platelet-Rich Plasma In Vitro

Abstract: IntroductionExtracorporeal shockwave therapy (ESWT) and platelet-rich plasma (PRP) are common treatments for soft tissue injuries in horses. Shockwave triggers cell specific responses to promote healing. Growth factors released from PRP also promote healing. It has been hypothesized that greater growth factor release would amplify the healing process. The combination of ESWT and PRP could promote healing in injured tendons and ligaments in the horse. The objective of this study was to determine if application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
0
17
0
4
Order By: Relevance
“…In the past, the mechanism by which ESWT acts on musculoskeletal diseases was assumed to be mechanical decomposition, just like extracorporeal shock wave lithotripsy. However, further clinical observations and experimental results, have suggested that ESWT can promote neovascularization, the release of growth factors, the differentiation of mesenchymal stem cells and the production of endogenous nitric oxides (NOs) [46][47][48], which can decrease the intrinsic stiffness of connective tissue, increase muscle elongation, improve tissue microcirculation and change the formation of neuromuscular junctions of the peripheral nervous system [49][50][51], in order to achieve encouraging clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the mechanism by which ESWT acts on musculoskeletal diseases was assumed to be mechanical decomposition, just like extracorporeal shock wave lithotripsy. However, further clinical observations and experimental results, have suggested that ESWT can promote neovascularization, the release of growth factors, the differentiation of mesenchymal stem cells and the production of endogenous nitric oxides (NOs) [46][47][48], which can decrease the intrinsic stiffness of connective tissue, increase muscle elongation, improve tissue microcirculation and change the formation of neuromuscular junctions of the peripheral nervous system [49][50][51], in order to achieve encouraging clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Este procedimiento permite la separación del plasma de los otros componentes sanguíneos, logrando obtener al finalizar un pool de plasma puro y rico en plaquetas, que para este trabajo tuvo una concentración de 1,5 X 10 6 plaquetas. (11) . Para la elaboración del hidrogel, se preparó la solución de β-quitosano 1,5% (p/v) en ácido acético 2% (v/v) 12,13 , luego se adicionó LP al 6 % o 12 % (v/v) hasta homogeneizar con ayuda de un agitador magnético.…”
Section: Elaboración Del Hidrogel Incubación Y Cuantificación De Pdgunclassified
“…Para esto, se congeló a -70 °C por 12 horas y descongeló a 37 °C (aproximadamente 10 minutos), lo que se denomina un ciclo. Después de tres ciclos, se centrifugó la muestra a 2500 rpm durante 15 minutos; el sobrenadante es el LP(11) . Plasma recolectado tras plasmaféresis por centrifugación de flujo discontinuo Para obtener el LP, se tomó 10 mL del PRP y sometió a un shock de temperatura para lisar de plaquetas.…”
unclassified
“…The biological effects of LIPUS and PRP presented in table 1. PRP-therapy can be combined with LNP and LIPUS resulting in augmentation of its effects due to the same target-effects and hypothetic phenomenon of ultrasonic intracavernous platelets activation [2,7]. Local negative pressure (LNP) therapy shall be considered as an auxiliary method to PRP and LIPUS due to its ability to slow down PRP outflow from injection zones.…”
mentioning
confidence: 99%